STUDI EFEKTIVITAS PENANGANAN TERAPI MUSIK TERHADAP PERUBAHAN PERILAKU MAHASISWA PEMINATAN TERAPI MUSIK - Levina Xaveria (MANASA, 2012)
It is very important for music therapist students to have effective characters andbehaviors in doing sessions with clients, as well as in his/her education process. Therefore, the purpose of this study is to find further influence of music therapy treatment in changing music therapy student’s behavior to be more effective as they become future music therapists. The first assessment tool is EPPS Personality Test (Edward Personal Preference Schedule) that was given to nine music therapy students. It had been known from the test, there are two students who were considered to receive a music therapy intervention because the basic needs they have to take care of. The second assessment tool is Behavior Observation Sheet developed by the researchers, that quantifies changes in those student’s behavior in music therapy practical class. The therapy techniques used in this research are improvisation, lyric analysis and song writing. The result proved that music therapy treatment is increasing the average points in the Behavior Observation Sheet. The therapy is effective to help student cognitively to be more aware about his/her self-potentials to solve problems.